Wages and the Great War: Evidence from the largest draft lottery in history - Bruno Caprettini; Hans-Joachim Voth (University of Zurich, Department of Economics, 2023)
Do veterans earn less? During WW I, the US organized "the greatest human lottery in history": a random draft of 24 million men. Ultimately, 2.8 million Americans were selected to join the armed forces. We sample 10% of registrants of the 1917 lottery and match these men with the 1930 and 1940 US Federal Censuses. Low lottery numbers significantly increased the likelihood of serving in World War I. Importantly, military service also had a positive causal effect on earnings and occupational outcomes. Veterans joined professions with higher cognitive skill requirements, including higher intelligence, language, reasoning, and math requirements. Randomly-assigned military service had fundamentally different effects during World War I than in Vietnam. We rationalize this finding by analyzing complier characteristics.
Keywords: N42; J45; I23; J24; N32; 330; Veterans' income; lottery; IV; effect of war participation